Supervision of Non-Profit Organizations (NPO) On Potential Criminal Acts of Money Laundering and Terrorist Financing - Hasan, Fuad (Corruptio, 2024)
The biggest challenge for NPOs is how the purpose of the NPO, to serve the community, can be run by legal corridors and not be used as a medium for money laundering for criminals or terrorism funding. Supervision of NPOs has a very important purpose in the context of preventing terrorism financing and also in the context of preventing money laundering. Therefore, the identification of donor recipients or beneficiaries for NPOs needs to be analyzed by looking at the existing regulatory framework, and whether the regulatory framework can effectively prevent money laundering and terrorism financing. This paper aims to discuss the supervision mechanism of NPOs in mitigating money laundering and terrorism financing, as well as the liability of NPOs if used as a medium for Money Laundering or Terrorist Financing. The research in this paper is Normative Research with Explanatory Descriptive Research Typology. The data analysis technique that the author uses is data analysis with a qualitative approach. Based on the research conducted by the author, it can be concluded that to prevent NPO funding from being misused for money laundering or terrorist financing, by way of supervision of the transaction flow of Mass Organizations as customers by the financial service provider through the identification and verification of donors and recipients or beneficial owner of NPO, and by the risk-based supervision of NPOs conducted by the Ministry that has authority to allow the establishment of NPOs through educating, monitoring and evaluation.